First Record of Alternaria pogostemonis: A Novel Species Causing Leaf Spots in Pogostemon cablin - Mei Luo; Minping Zhao; Yinghua Huang; Jiawei Liu; Qiurong Huang; Yongxin Shu; Zhangyong Dong (Pathogens, 2022)
Pogostemon cablin (Lamiaceae) is a component of traditional medicines in Southern China. The identification of P. cablin pathogens is essential for the production and development of this industry. During 2019–2020, a leaf spot on P. cablin was observed in Zhanjiang, Guangdong Province. The pathogen of the leaf spot was isolated and identified using morphological and phylogenetic methods. Phylogenetic analysis was performed using the internal transcribed spacer (ITS) region, glyceraldehyde-3-phosphate dehydrogenase (gapdh), RNA polymerase II (rpb2), translation extension factor 1-alpha (tef1), and Alternaria major allergen 1 (Alt-a1) genes. Based on phylogenetic and morphological studies, this was confirmed to be a novel species of Alternaria pogostemonis, with description and illustrations presented. The pathogenicity test of A. pogostemon was verified by Koch’s postulates as causing leaf spot disease. This is the first report of leaf spot disease in P. cablin caused by the Alternaria species. This study contributes to the knowledge of P. cablin leaf spot diseases.